Policy Options to Reduce Fragmentation in the Pooling of Health Insurance Funds in Iran - Mohammad Bazyar; Arash Rashidian; Sumit Kane; Mohammad Reza Vaez Mahdavi; Ali Akbari Sari; Leila Doshmangir (Kerman University of Medical Sciences, 2016)
There are fragmentations in Iran's health insurance system. Multiple health insurance funds exist, without adequate provisions for transfer or redistribution of cross subsidy among them. Multiple risk pools, including several private secondary insurance schemes, have resulted in a tiered health insurance system with inequitable benefit packages for different segments of the population. Also fragmentation might have contributed to inefficiency in the health insurance systems, a low financial protection against healthcare expenditures for the insured persons, high coinsurance rates, a notable rate of insurance coverage duplication, low contribution of well-funded institutes with generous benefit package to the public health insurance schemes, underfunding and severe financial shortages for the public funds, and a lack of transparency and reliable data and statistics for policy-making. We have conducted a policy analysis study, including qualitative interviews of key informants and document analysis. As a result we introduce three policy options: keeping the existing structural fragmentations of social health insurance (SHI) schemes but implementing a comprehensive "policy integration" strategy; consolidation of existing health insurance funds and creating a single national health insurance scheme; and reducing fragmentation by merging minor well-resourced funds together and creating two or three large insurance funds under the umbrella of the existing organizations. These policy options with their advantages and disadvantages are explained in the paper.